2023
DOI: 10.25105/jipak.v18i1.12396
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Financial Distress, Thin Capitalization, Karakteristik Eksekutif, Dan Multinationality Terhadap Praktik Tax Avoidance Pada Perusahaan Properti Dan Real Estate

Abstract: The rise of tax avoidance today is one of the foundations of research carried out. Many tax avoidance schemes are carried out by enterprises.The practice of tax avoidance is an act of tax avoidance that takes advantage of loopholes in the tax law. For this reason, this study aims to estimate and analyze how the influence of financial distress, thin capitalization, executive characteristics and multinationality on tax avoidance practices during the 2015 - 2020 period. Using the Panel data method on companies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…It is found that there is a significant influence between income smoothing and tax avoidance. The same thing was also stated by The act of tax avoidance has an impact on the strategy of profit manipulation employed by businesses [13]. It is stated that variations between tax regulations and accounting principles related to profit recognition provide management with opportunities to manipulate profits.…”
Section: Introductionmentioning
confidence: 81%
“…It is found that there is a significant influence between income smoothing and tax avoidance. The same thing was also stated by The act of tax avoidance has an impact on the strategy of profit manipulation employed by businesses [13]. It is stated that variations between tax regulations and accounting principles related to profit recognition provide management with opportunities to manipulate profits.…”
Section: Introductionmentioning
confidence: 81%